2016
DOI: 10.1002/2015jb012627
|View full text |Cite
|
Sign up to set email alerts
|

Submarine groundwater discharge as a possible formation mechanism for permafrost‐associated gas hydrate on the circum‐Arctic continental shelf

Abstract: Submarine groundwater discharge (SGD) is a large‐scale, buoyancy‐driven, offshore flow of terrestrial groundwater. If SGD occurs within the permafrost‐bearing sediments of the circum‐Arctic shelf, such fluid circulation may transport large amounts of dissolved methane to the circum‐Arctic shelf, aiding the formation of permafrost‐associated gas hydrate. We investigate the feasibility of this new permafrost‐associated gas hydrate formation mechanism with a 2‐D, multiphase fluid flow model, using the Canadian Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The last finding of this study was that submarine groundwater discharge at this site was largely buoyancy-driven, as fresh groundwater is less dense than the corresponding seawater [10]. Frederick and Buffet built upon this work with a later paper, where they explored the ability of submarine groundwater discharge to aid in methane hydrate expansion by delivering methane to the cold continental shelf sediments using a numerical model of two-phase flow of pore fluids, based on the finite volume method [50]. They found that in subpermafrost areas, groundwater flow did assist in the development of methane hydrate formation, even if the groundwater was undersaturated with respect to methane [50].…”
Section: Marine Sitesmentioning
confidence: 99%
See 4 more Smart Citations
“…The last finding of this study was that submarine groundwater discharge at this site was largely buoyancy-driven, as fresh groundwater is less dense than the corresponding seawater [10]. Frederick and Buffet built upon this work with a later paper, where they explored the ability of submarine groundwater discharge to aid in methane hydrate expansion by delivering methane to the cold continental shelf sediments using a numerical model of two-phase flow of pore fluids, based on the finite volume method [50]. They found that in subpermafrost areas, groundwater flow did assist in the development of methane hydrate formation, even if the groundwater was undersaturated with respect to methane [50].…”
Section: Marine Sitesmentioning
confidence: 99%
“…Frederick and Buffet built upon this work with a later paper, where they explored the ability of submarine groundwater discharge to aid in methane hydrate expansion by delivering methane to the cold continental shelf sediments using a numerical model of two-phase flow of pore fluids, based on the finite volume method [50]. They found that in subpermafrost areas, groundwater flow did assist in the development of methane hydrate formation, even if the groundwater was undersaturated with respect to methane [50]. However, the results of hydrate formation were inconsistent within areas of continuous permafrost, and relied more on permafrost extent [50].…”
Section: Marine Sitesmentioning
confidence: 99%
See 3 more Smart Citations